A case-control study evaluating CT signs of xiphoid process associated with xiphodynia - Ryosuke Ono; Ken Horibata (PLoS ONE, 2025)
This study assessed whether CT signs of the xiphoid process, such as the xiphisternal angle and soft tissue compression, are useful for diagnosing xiphodynia. Conducted as a case-control study within a cohort, it involved 1560 participants who visited a small urban hospital in Japan for chest or abdominal pain between January 2021 and September 2023. From this group, patients who underwent CT scans that included the xiphoid process were selected. The study group consisted of nine individuals diagnosed with xiphodynia, while the control group included 321 individuals diagnosed with other causes of pain. No significant differences were found in the xiphisternal angle, soft tissue compression, or xiphoid tip features between the groups. However, in about 70% of cases, the xiphoid process curved forward and then backward. These findings suggest that the xiphisternal angle is not a useful marker for diagnosing xiphodynia, and that the curvature of the xiphoid process is common regardless of the condition.